The Baptist World Alliance and Antisemitism: An Historical Overview - Spitzer, Lee B. (Journal of European Baptist Studies, 2021)
This historical study investigates how the Baptist World Alliance responded to the struggles of the Jewish people throughout the twentieth and twenty-first centuries in light of Baptist core convictions, as expressed in World Congress and General Council resolutions and statements. As a collection, the past resolutions, statements and messages of the Baptist World Alliance indicate that the Jewish people were given only minimal attention until the rise of Hitler and Nazism. Responding to that challenge, antisemitism as a manifestation of racism became a recurring theme in Baptist pronouncements. After the Holocaust and the establishment of Israel, the BWA strove to articulate a balanced and nuanced position concerning the conflict between Israel and the Palestinians (and terrorism), while avoiding any consideration of how antisemitism might play a role in the conflict. With the rise of twenty-first century antisemitism, in 2019 the BWA returned to its historical roots and once again expressed friendship with the Jewish people and opposed antisemitism.